Effect of giving Extract Ethanol from Bitter Gourd Fruit (Momordica Charantia L) on the Quality and Quantity of Mouse Spermatozoa (Mus Musculus) - Zul Hendry; Radliyatul Fahmi (Lembaga Pengembangan Kinerja Dosen, 2023)
Men's participation in the Family Planning (KB) program is still very minimal due to the limited choice of contraceptive methods. Efforts need to be made to develop contraceptive methods, one of which is using natural ingredients. Bitter melon (Momordica charantia L) is known to have potential benefits as a male antifertility agent. This research used an experimental design with a sample size of 20 mice divided into 4 groups randomly. Treatment groups 1-3 were given different doses, namely 100, 80, 60 mg of bitter melon ethanol extract/100g BW/day, and the control group was given distilled water for 35 days. The mice were sacrificed the day after the last dose, then spermatozoa were collected from the epididymis and their number, motility, viability and morphology were examined. The results of this study showed a significant decrease in the number and motility of spermatozoa and was directly proportional to the size of the dose given. In terms of viability parameters, there was a significant decrease at all doses. Meanwhile, for spermatozoa morphology, only a dose of 100 mg had a significant impact. The conclusion from the results of this research is that giving bitter melon fruit extract has an effect on the number, motility, viability and morphology of spermatozoa. The most effective dose is 100 mg/100 gBB/day.